Função normativa da administração: uma análise acerca do fenômeno da deslegalização - Yara de Melo Miranda Gonzaga (2014)
The exercise of normative activity by Public Authorities is a phenomenon which has been observed and expanded over time. After the overcoming of the Liberal State, the passage through the Welfare State and the entrance to the domain of the Regulatory State this normative role has become more apparent, especially with the advent of regulatory agencies, introduced, at least under that name, by the State Reform put into effect by the Law 8.031/90 - replaced by the Law 9.491/97 - which established the National Privatization Program with the main purpose of transferring to the private sector the activities which had been unduly explored by the public sector. The present work aimed to study the regulatory function of Public Authorities, closely to the understanding of the delegalization phenomenon. It started, therefore, from the analysis of the functions of the State, going through the analysis of the evolution of the separation of powers and legality, which we advocate do not present the same content as at the time of bourgeois revolutions, which put them into effect, making necessary the reading of both in the light of modernity in order to accommodate them to the reality of the current State. From the examination of important doctrine exponents who deal with the issue of delegalization and judicial precedents on the matter, we seek to find a constitutional basis for the legitimation of normative delegation, moving it away from opposite positions and proposing a new concept for the institute, aspiring to frame the necessary requirements to its own legitimacy.